The best cooperative team building activities for all ages and organization - Michaelis, Bill; Holland, Ezra ([S.l. : s.n.], 2003)
Contains over 20 proven accessible activities such as arrows, commonalities, high 5 partners, prominate, atandoff, human spring and etc., plus variations, written rules, leadership and processing hints, followup resources and etc. a modeled sequence of cooperative behaviors and group builing linked with applications for school, work, play and life
Title from title screen
Keywords: Work groups; Teams in the workplace